The Role of Mitochondria in Cellular Energy Production and Bioenergetic Regulation: A Qualitative Meta-Analysis - Mala, Nurfadila; Mala, Benedikta Odaliva; Papa, Florentina Christiani; Hayon, Melkior Bala; Wae, Veronika P. Sinta Mbia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Mitochondria play a central role in cellular energy production through oxidative phosphorylation that generates ATP, while also regulating metabolism, organelle dynamics, and bioenergetic signal integration. This study aims to synthesize the role of mitochondria in cellular bioenergetics through a qualitative meta-analysis of scientific articles published between 2015 and 2025. The PRISMA approach was applied for systematic article selection, resulting in 30 relevant articles analyzed for key findings. The synthesis shows that mitochondria do not operate in isolation but form a functional network that adjusts ATP production according to the specific energy demands of the cell. Mitochondrial fusion-fission dynamics influence energy distribution efficiency, while metabolic regulation and interactions with other organelles maintain cellular energy homeostasis. Mitochondrial dysfunction is associated with neuromuscular disorders, aging, and degenerative diseases including cancer. The study concludes that mitochondria are adaptive bioenergetic centers, playing a crucial role in maintaining energy efficiency and providing a scientific basis for further research in cellular biology, biomedicine, and energy-based therapeutic applications. This synthesis expands understanding of mitochondrial bioenergetic mechanisms and their implications for health and biotechnology applications.